2011
DOI: 10.1007/s00595-011-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative tetanus after laparoscopic obturator hernia repair for strangulated ileus: report of a case

Abstract: This report presents the case of an 84-year-old woman who developed tetanus 3 days after the resection of a gangrenous small intestine caused by obturator hernia incarceration. The diagnosis of tetanus was clinically made after the appearance of generalized spastic contractions with opisthotonus. Clostridium tetani organisms residing in the gastrointestinal tract were presumed to have been endogenously inoculated into the strangulated intestine, where it produced tetanospasmin, causing tetanus. The patient suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…We regret that in our case no stool sample was taken before the antibiotics were started. Most of the reported cases of postoperative tetanus are from patients who underwent abdominal surgery 3 7 11–16. In these cases surgery does not have to breach the gastrointestinal tract 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We regret that in our case no stool sample was taken before the antibiotics were started. Most of the reported cases of postoperative tetanus are from patients who underwent abdominal surgery 3 7 11–16. In these cases surgery does not have to breach the gastrointestinal tract 12.…”
Section: Discussionmentioning
confidence: 99%
“…They hypothesise that the patient did not have protective immunity against tetanus and that her course was benign as a consequence of passive immunisation from the transfusions before surgery. After this case report, only one new case of tetanus after gastrointestinal surgery was published in 2012,14 which approves the ‘forgotten pathogen’ status.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of tetanus was made only when opisthotonus in this patient became evident and normal tetanus treatment proved to be successful. In another case (Mori et al, 2012), an 84-year-old woman developed tetanus 3 days after the resection of a gangrenous small intestine caused by obturator hernia incarceration. The diagnosis of tetanus was made clinically after the appearance of generalized spastic contractions with opisthotonus.…”
Section: Discussionmentioning
confidence: 99%
“…The usual port of entry is through a break in the skin, and risk factors for acquiring tetanus are related to clinical conditions that include this, especially surgical site wounds. Although rare, the gastrointestinal tract can provide a possible endogenous source of C. tetani (Mori et al, 2012).…”
mentioning
confidence: 99%
“…Several studies have demonstrated cases of generalized tetanus where the point of entry remains iatrogenic, following medical care, especially after mastectomy [ 8 ], following replantation of an amputated finger [ 9 ], after laparotomy [ 10 , 11 ] and laparoscopic procedure [ 12 ], and even following tooth extraction [ 13 ].…”
Section: Introductionmentioning
confidence: 99%